2021
DOI: 10.3390/en14217023
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Analysis Using Fuzzy Logic for Detection and Monitoring of COVID-19 Patients

Abstract: Recent developments regarding the Internet of Things (IoT), Artificial Intelligence (AI), and Machine Learning (ML) opened new horizons of healthcare opportunities. Moreover, these technological advancements give strength to face upcoming healthcare challenges. One of such challenges is the advent of COVID-19, which has adverse effects beyond comprehension. Therefore, utilizing the basic functionalities of IoT, this work presents a real-time rule-based Fuzzy Logic classifier for COVID-19 Detection (FLCD). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The fusion strategy was the most potent for estimation, with an accuracy of 95.56 ± 0.57%, recall of 95.61 ± 0.79%, precision of 95.5 ± 0.61%, F-score of 95.55 ± 0.57%, specificity of 95.61 ± 0.81%, and MCC of 91.12 ± 1.15% compared to other feature extraction procedures. (6)(7)(8) contain a list of all the SVM models' performance outcomes. Based on the investigational consequences for all three scenarios, it can be confirmed that the features combined from the HOG and LPQ techniques performed better than the other scenarios using the SVMP, SVML, and SVMRBF classifiers.…”
Section: Discussion Of Experiments Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fusion strategy was the most potent for estimation, with an accuracy of 95.56 ± 0.57%, recall of 95.61 ± 0.79%, precision of 95.5 ± 0.61%, F-score of 95.55 ± 0.57%, specificity of 95.61 ± 0.81%, and MCC of 91.12 ± 1.15% compared to other feature extraction procedures. (6)(7)(8) contain a list of all the SVM models' performance outcomes. Based on the investigational consequences for all three scenarios, it can be confirmed that the features combined from the HOG and LPQ techniques performed better than the other scenarios using the SVMP, SVML, and SVMRBF classifiers.…”
Section: Discussion Of Experiments Resultsmentioning
confidence: 99%
“…However, the fusion technique with the SVMP classifier have delivered an extremely maximum average accuracy of 97.15 ± 0.38% among the remaining classifiers for all scenarios. The misclassification error rate indicator was included in this work to evaluate the performance of the suggested scenarios, as revealed in Figure (8). The consequences presented that combining HOG and LPQ feature sets to the SVM classifier with a polynomial kernel produced a lowest misclassification error of 2.85%, demonstrating that the suggested scenario operates significantly better than earlier suggested scenarios.…”
Section: Discussion Of Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have seen the utilization of neural networks, evolutionary computing, and fuzzy systems in this area. In the particular case of fuzzy logic, we can find that most of the works in the literature for monitoring are based on the simplest form of fuzzy logic [1][2][3], which is called type-1, like the works that can be reviewed in [4][5][6][7][8][9][10][11][12]. More recently, type-2 has also been considered in this area, as a way to model uncertainty in a better fashion and achieve better results, as can be verified in [13,14].…”
Section: Introductionmentioning
confidence: 95%